2019
DOI: 10.4236/ce.2019.1012187
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Questioning Skills through <i>Hikmah</i> (Wisdom) Pedagogy

Abstract: The ability to ask and answer questions is central to learning. Questioning is one of the thinking processes that can stimulate critical thinking among students. However, it can be seen that students have yet to master the questioning skill and are still in the lower order thinking (LOTs) questions. Therefore, this research aims to improve students questioning after the implementation of Hikmah Pedagogy. The research will reveal student's improvement in critical thinking through the evidence from student's que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Nevertheless, there was no significant difference in manners in the community of inquiry. The findings also coincide with Hashim et al, (2019) Hashim et al (2017) supported that there were statistically significant differences in listening and speaking and manners in the community of inquiry. However, no significant differences were found in reasoning and openmindedness.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, there was no significant difference in manners in the community of inquiry. The findings also coincide with Hashim et al, (2019) Hashim et al (2017) supported that there were statistically significant differences in listening and speaking and manners in the community of inquiry. However, no significant differences were found in reasoning and openmindedness.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies on Hikmah (Wisdom) pedagogy focused on its influence in enhancing critical thinking (Hashim & Wan Yusoff, 2006;Othman & Hashim, 2007, Abdullah, 2009Hashim et al, 2017;Wan Yusoff, Hashim, Khalid, Hussein, & Kamaluddeen, 2018;Zulkifli & Hashim, 2020). Other studies highlighted qualitative research (Zulkifli & Hashim, 2020) while fewer studies concentrated on Hikmah pedagogy in questioning skills (Zulkifli & Hashim, 2019;Juperi, 2011;Alias, 2017).…”
Section: Revista De Ciencias Sociales Y Humanidadesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to determine the extent of students' questioning skills in class and also to determine the level of the questions given. The second researcher (Zulkifli & Hashim, 2019), the Development of Questioning Skills through Hikmah (Wisdom) Pedagogy The results showed that an improvement where the students were able to produce questions from lower order thinking questions(LOTs) to higher order thinking questions (HOTs) according to Hierarchy of Bloom's Taxonomy. This research recommends teacher to apply Hikmah Pedagogy in order to enhance critical thinking among students.…”
Section: Firmansyah and Satamentioning
confidence: 99%
“…Questioning refers to strategies of collecting and understanding information about students' development, ability and competency (Astrid et al, 2019). This questioning activity in classroom is important to develop students critical thinking, creative thinking ability, and higher level thinking skills (Shaunessy, 2005;Zulkifli & Hashim, 2019). Padmadewi, Artini and Agustini (2017) add that the purpose of questioning is to develop students' interests and curiosity, to get student attention, to evaluate student preparation, to review and summarize previous lessons or subtopics, to assess student achievement, diagnose student difficulties in the learning process, and to motivate and attract student activity.…”
Section: Introductionmentioning
confidence: 99%